Analisis Pengaruh Likuiditas, Pertumbuhan Aset, dan Ukuran Perusahaan terhadap Profitabilitas Perusahaan Syariah: Studi Empiris pada Perusahaan yang Tergabung Dalam Index JII Periode 2020 – 2023 - Sucayono, Sucayono; Soeyatno, Rahmah Farahdita; Julianto, Viktor Waruntung (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This research aims to analyze the influence of liquidity, asset growth and company size on the profitability of companies in the JII index listed on the Indonesia Stock Exchange during the 2020-2023 period. Based on the purposive sampling method, this research used fourteen companies as research samples. The analytical method used in this research is multiple regression analysis carried out with the help of SPSS software. The results of this research show that liquidity, asset growth and company size have a significant effect on profitability simultaneously. The results of this research also show that asset growth has a significant effect on profitability, while liquidity and company size do not have a significant effect on the profitability of companies in the JII index listed on the Indonesia Stock Exchange during the 2020-2023 period.